Coriandrum sativum L., essential oil as a promising source of bioactive compounds with GC/MS, antioxidant, antimicrobial activities: in vitro and in silico predictions - Nouioura, Ghizlane; El fadili, Mohamed; El Hachlafi, Naoufal; Maache, Souad; Mssillou, Ibrahim; A. Abuelizz, Hatem; Lafdil, Fatima Zahra; Er-rahmani, Sara; Lyoussi, Badiaa; Derwich, Elhoussine (Frontiers in Chemistry, 2024)
This exploratory study aims to identify the volatile compounds in Coriandrum sativum L. essential oil (CS-EO) and evaluate its antioxidant and antimicrobial properties in vitro. The processes underlying the in vitro biological properties were explained using in silico simulations, including drug-likeness prediction, molecular docking, and pharmacokinetics (absorption, distribution, metabolism, excretion, and toxicity-ADMET). Gas chromatographymass spectrometry (GC-MS) was utilized for the chemical screening of CS-EO. The antioxidant activity of CS-EO was evaluated using five in vitro complementary techniques, including 2,2diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) radical scavenging activity, β-Carotene bleaching test (BCBT), reducing power (RP), and phosphomolybdenum assay (TAC). GC-MS analysis revealed that the primary components of CS-EO are linalool (59.04%), followed by γ-Terpinene (13.02%) and α-Pinene (6.83%). The results of the in vitro antioxidant assays indicate that CS-EO exhibits a superior antioxidant profile, showing estimated scavenging rates of 1.52±0.14 mg/mL, 0.51±0.04 mg/mL for ABTS + , and 9.02±0.01 mg/mL for BCBT. C. sativum exhibited reducing power (RP) and total antioxidant activity (TAC) of 6.13±0.00 µg/mL and 213.44±0.45 mg AAE/mL, respectively.The in vitro antimicrobial activity of CS-EO was assessed against five strains, including two gram-positive bacteria, two gram-negative bacteria, and one fungal strain (Candida albicans).The disc-diffusion assay revealed significant antibacterial and antifungal activities against all strains, with zones of inhibition exceeding 15 mm. The microdilution test highlighted the lowest MIC and MBC values with gram-positive bacteria, ranging from 0.0612 to 0.125 % v/v for MIC and 0.125% v/v for MBC. For the fungal strain, MIC was recorded at 0.5% and MFC at 1.0% v/v. CS-EO demonstrates bactericidal and fungicidal activity based on the MBC/MIC and MFC/MIC ratios. According to the ADMET study, the primary CS-EO compounds have advantageous pharmacokinetic characteristics, making them a suitable candidate for the development of pharmaceutical drugs. These findings provide empirical support for the traditional uses of this plant and indicate its possible use as a natural remedy. It holds promise for large-scale utilization as an environmentally friendly preservative within the food and agriculture industries, effectively countering fungal growth and aflatoxin contamination in stored commodities.